2009
DOI: 10.1016/j.molcel.2009.07.025
|View full text |Cite
|
Sign up to set email alerts
|

KEAP1 E3 Ligase-Mediated Downregulation of NF-κB Signaling by Targeting IKKβ

Abstract: SUMMARY IκB kinase β (IKKβ) is involved in tumor development and progression through activation of the nuclear factor (NF)–κB pathway. However, the molecular mechanism that regulates IKKβ degradation remains largely unknown. Here, we show that a Cullin 3 (CUL3)–based ubiquitin ligase, Kelch-like ECH-associated protein 1 (KEAP1), is responsible for IKKβ ubiquitination. Depletion of KEAP1 led to the accumulation and stabilization of IKKβ and to up-regulation of NF-κB–derived tumor angiogenic factors. A systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
285
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(300 citation statements)
references
References 21 publications
15
285
0
Order By: Relevance
“…BARD analogues promote activation of Nrf2 via covalent modification of the specific thiols in the Keap1 molecules [26]. In addition to repression of Nrf2, Keap1 participates in repression of IKKB (the positive regulator of NF-k B) by facilitating its proteasomal degradation [55]. Accordingly oxidative or covalent modification of Keap1 can lead to release of IKKB, phosphorylation of IKB (the NF k B inhibitor) by IKKB, dissociation of IKB-NF k B complex, and nuclear translocation of NF k B, events that trigger transcriptional upregulation of pro-inflammatory and pro-fibrotic mediators.…”
Section: Discussionmentioning
confidence: 99%
“…BARD analogues promote activation of Nrf2 via covalent modification of the specific thiols in the Keap1 molecules [26]. In addition to repression of Nrf2, Keap1 participates in repression of IKKB (the positive regulator of NF-k B) by facilitating its proteasomal degradation [55]. Accordingly oxidative or covalent modification of Keap1 can lead to release of IKKB, phosphorylation of IKB (the NF k B inhibitor) by IKKB, dissociation of IKB-NF k B complex, and nuclear translocation of NF k B, events that trigger transcriptional upregulation of pro-inflammatory and pro-fibrotic mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these cysteine residues are candidate sites for thiocarbamoylation by ITCs, although direct evidence for covalent binding to NF-B subunits by this class of molecule is lacking. Very recent studies have demonstrated that, in addition to Nrf2, Keap1 can function as a ubiquitin E3 ligase for IKK and thereby downregulate NF-B activity [55]. However, it is not known whether modulation of Keap1 by ITCs per se leads to increased expression/activity of IKK.…”
Section: Hif-independent Control Of Angiogenesismentioning
confidence: 99%
“…One of the Keap1 substrates for ubiquitination is Ikkβ which upregulates the Nf-κB transcription factor through the negative regulation of its inhibitor Ikbα. 9 Under oxidative stress, Ikkβ is released from Keap1, and mediates the activation of Nf-kB regulated genes, resulting in increased growth, proliferation and anti-apoptosis, thus contributing to cell survival and tumor progression. 10 Moreover, recent studies suggest that under oxidative stress conditions Keap1 modulates the intrinsic apoptotic pathway through the degradation of Bcl2 and Bcl-xL antiapoptotic proteins.…”
Section: Introductionmentioning
confidence: 99%